2012
DOI: 10.20965/jaciii.2012.p0793
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Bag-of-Features for Scalable Map Retrieval

Abstract: Retrieving a large collection of environment maps built by mapper robots is a key problem in mobile robot self-localization. The map retrieval problem is studied from the novel perspective of the multi-scale Bag-Of-Features (BOF) approach in this paper. In general, the multi-scale approach is advantageous in capturing both the global structure and the local details of a given map. BOF map retrieval is advantageous in its compact map representation as well as the efficient map retrieval using an inverted file s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A notable exception is several shape descriptors, including shape context employed in our previous studies [15], and the polestar descriptor shown above, by which size information is explicitly included in the descriptor, which makes it possible to distinguish those objects with different sizes. Among them, this study employs polestar descriptor as it was successful in its vector quantized form (i.e., bag-of-words model) in our previous study [10].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…A notable exception is several shape descriptors, including shape context employed in our previous studies [15], and the polestar descriptor shown above, by which size information is explicitly included in the descriptor, which makes it possible to distinguish those objects with different sizes. Among them, this study employs polestar descriptor as it was successful in its vector quantized form (i.e., bag-of-words model) in our previous study [10].…”
Section: Related Workmentioning
confidence: 99%
“…We adopt the polestar feature for our purpose because it has several desirable properties, including viewpoint invariance and rotation independence, and has proven effective as a landmark for map matching in previous studies [10]. The extraction algorithm consists of three steps ( Fig.…”
Section: Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…We adopt the polestar feature for our purpose because it has several desirable properties, including viewpoint invariance and rotation independence, and has proven effective as a landmark for map matching in previous studies [10]. The extraction algorithm consists of three steps ( Fig.2): (1) First, a set of keypoints are sampled from the raw 2D scan points.…”
Section: A Feature Extractionmentioning
confidence: 99%